Analysis Influence Marketing Mix on Purchase Decision Wardah Skincare Brand - Hasni, Hasni; Sujana, I Wayan (Institute for Research and Community Service, 2023)
Due to the large number of requests, Wardah expanded sales of its products in Baubau City to traditional markets, supermarkets and mini markets, one of which is Toko Liwanda. Skincare sales at the Liwanda Store are very rapid, including Wardah products. This is evidenced by the achievement of its sales target in January-July 2022, Wardah products sold at the Liwanda Store always reach their sales target. However, in May-July it experienced active fluctuations. Wardah Brand Skincare products have a sales target above the dominance of 60%, meaning that Wardah Skincare has an active role in selling wardah products at the Liwanda Store. Good sales will affect marketing both in terms of the marketing mix or the decisions of buyers. This study aims to determine and analyze the influence of the marketing mix on purchasing decisions of Skincare Brand Wardah at Liwanda Stores. The population in this study was 1,058 people. By determining the sample using non-probability sampling and the slovin formula to get a total of 91 respondents. Methods of data collection using a questionnaire or questionnaire. The analytical method in this study uses simple linear regression. The results of the research on testing the marketing mix variable hypothesis show that the tcount value is greater than ttable, (2.171 > 1.662), or sig smaller than α (0.003 <0.05), so the marketing mix partially has a real influence on Wardah Skincare purchasing decisions in Liwanda shop.